2018
DOI: 10.1007/s00701-018-3639-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for post-traumatic hydrocephalus following decompressive craniectomy

Abstract: Our results showed that delayed cranial reconstruction was associated with an increasing rate of PTH after DC. The presence of an interhemispheric hygroma was an independent predictive radiological sign of PTH in decompressed patients for severe TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 19 publications
1
38
1
Order By: Relevance
“…In 11 studies (comparative case control or cohort), we asked whether early CP (i.e., CP ≤3 months) versus later CP differently impacted the rate of hydrocephalus following DC [ Table 1]. [1][2][3][4][5]7,9,[10][11][12]14] Statistical method for meta-analysis e meta-analysis was performed using STATA/IC 13.1 statistical package (StataCorp LP, College Station, TX, USA). e log odds ratios (LORs) and 95% confidence intervals for each outcome were then reckoned as by "early" and "late" time points.…”
Section: Study Selection and Outcomementioning
confidence: 99%
See 2 more Smart Citations
“…In 11 studies (comparative case control or cohort), we asked whether early CP (i.e., CP ≤3 months) versus later CP differently impacted the rate of hydrocephalus following DC [ Table 1]. [1][2][3][4][5]7,9,[10][11][12]14] Statistical method for meta-analysis e meta-analysis was performed using STATA/IC 13.1 statistical package (StataCorp LP, College Station, TX, USA). e log odds ratios (LORs) and 95% confidence intervals for each outcome were then reckoned as by "early" and "late" time points.…”
Section: Study Selection and Outcomementioning
confidence: 99%
“…Ten studies were retrospective, and one study involved a prospective cohort. [1][2][3][4][5]7,9,[10][11][12]14] All papers were classified as level of evidence "IIIB. "…”
Section: Inclusion Of Eleven Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We studied with keen interest the article by Nasi et al regarding the risk factors for post-traumatic hydrocephalus (PTH) after decompressive craniectomy in traumatic brain injury patients and their 6-month clinical outcomes [2].…”
Section: Dear Editormentioning
confidence: 99%
“…
Dear Editor,We studied with keen interest the article by Nasi et al regarding the risk factors for post-traumatic hydrocephalus (PTH) after decompressive craniectomy in traumatic brain injury patients and their 6-month clinical outcomes [2].We commend the authors on undertaking an evaluation of these risk factors as early prediction of hydrocephalus may facilitate early anticipatory management and result in a better long-term outcome vis-à-vis a late responsive intervention. In this study, the authors have found radiological finding of interhemispheric hygroma and delayed cranioplasty to be significantly associated with development of post-traumatic hydrocephalus.The predictive potential of interhemispheric hygroma has been reported by other authors as well.
…”
mentioning
confidence: 99%